Advances in real-world research on fertility preservation in men with malignant tumours - Ma, Dongsheng; Xi, Jianhong (Frontiers in Urology, 2025)
Malignant tumours have become one of the diseases that seriously threaten human health, and their incidence is increasing year by year. Worldwide, malignant tumours have become one of the most common causes of death in men. With the continuous progress of comprehensive oncological treatment, the cure rate and the survival rate of malignant tumours have been increasing, and the survival cycle has been prolonged, so the issue of fertility preservation in male malignant tumour patients has received widespread attention. In this review, researchers will discuss the real-world research progress related to fertility preservation in male malignant tumour patients, with a view to provide some reference basis for clinical decision-making.